2012
DOI: 10.1371/journal.pone.0048615
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase Linkers Are Optimized Based on Domain Type and Function: Insights from Sequence Analysis, Biophysical Measurements, and Molecular Simulation

Abstract: Cellulase enzymes deconstruct cellulose to glucose, and are often comprised of glycosylated linkers connecting glycoside hydrolases (GHs) to carbohydrate-binding modules (CBMs). Although linker modifications can alter cellulase activity, the functional role of linkers beyond domain connectivity remains unknown. Here we investigate cellulase linkers connecting GH Family 6 or 7 catalytic domains to Family 1 or 2 CBMs, from both bacterial and eukaryotic cellulases to identify conserved characteristics potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 89 publications
4
96
0
1
Order By: Relevance
“…We note that linkers in lignocellulose-degrading enzymes lack sequence conservation, which differs from some intrinsically disordered proteins that form secondary structure upon binding. However, despite this lack of sequence conservation, a recent study demonstrated that linker lengths, glycan positioning, and amino acid content are both conserved within a given GH family and are different between at least two GH families, namely GH6 and GH7 enzymes examined here (24). These results (24), when taken together with the present study, suggest that linker lengths and sequences may be optimized for a given binding affinity that is tuned based on the catalytic action of the overall enzyme.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…We note that linkers in lignocellulose-degrading enzymes lack sequence conservation, which differs from some intrinsically disordered proteins that form secondary structure upon binding. However, despite this lack of sequence conservation, a recent study demonstrated that linker lengths, glycan positioning, and amino acid content are both conserved within a given GH family and are different between at least two GH families, namely GH6 and GH7 enzymes examined here (24). These results (24), when taken together with the present study, suggest that linker lengths and sequences may be optimized for a given binding affinity that is tuned based on the catalytic action of the overall enzyme.…”
Section: Discussionmentioning
confidence: 68%
“…However, despite this lack of sequence conservation, a recent study demonstrated that linker lengths, glycan positioning, and amino acid content are both conserved within a given GH family and are different between at least two GH families, namely GH6 and GH7 enzymes examined here (24). These results (24), when taken together with the present study, suggest that linker lengths and sequences may be optimized for a given binding affinity that is tuned based on the catalytic action of the overall enzyme. Nature has evolved multiple strategies for combining binding and catalytic function in single proteins and protein complexes for degradation of plant cell walls, and the results obtained here are primarily relevant for multimodular, lignocellulose-degrading enzymes that contain sufficiently long, disordered linkers to bind to cellulose and exhibit glycosylation.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations